Satisfação do paciente com a fisioterapia :tradução, adequação cultura e validação de um instrumento de medida - Mendonça, Karla Morganna Pereira Pinto de (2004)
The measurement of patient satisfaction can provide information about the success of the care provider in reaching the values and meeting the expectations of the patient. The purpose of this study was to translate into the Portuguese language and to culturally customize to the Brazilian population the instrument to measure patient satisfaction with physical therapy elaborated by Goldstein et al. The study sample was made up of 279 patients who were undergoing physical therapy treatment at 39 different private clinics in a middle-sized town in northeastern Brazil. For the translation of the survey instrument, the back-translation technique was employed, in association with the bilingual method. The reliability and validity of the Brazilian version of the instrument were both assessed. Reliability analysis, carried out with the computation of Cronbach alpha coefficients, showed that the measures obtained with the instrument have a high degree of internal consistency. The aspects dealing with the patient therapist relationship are the most important predictors of satisfaction, followed by those dealing with courtesy, privacy, and practical aspects such as efficiency of the facility in the patient admissions process, setting up of appointments, and waiting time in waiting room. Items dealing with aspects such as location of the facility and availability of parking facilities may underestimate the reliability of the instrument. This study translated, culturally customized, and validated an instrument to measure patient satisfaction with physical therapy originally developed in English. By so doing, this study has made this instrument available to the Brazilian society, and it has rendered it a useful parameter that can be utilized in our country in the field of physical therapy